Red Nacional de Cultivares de Girasol. 2023/2024 [Conjunto de datos] - Llorens, María Clara (2024)
Localidad: Miramar (38°16'8.60"S, 57°49'54"O), Fuente: María Clara Llorens (CEI Miramar) -- Localidad: Pieres (37º46'15,6''S, 8º18'13,9''O), Fuente: Criadero Buck -- Localidad: Laprida (37°15'25"S, 60°49'37"O), Fuente: Lia Oyesqui (AER Olavarría), Kevin Leaden (AER Laprida) -- Localidad: Coronel Suarez (37º 25' 50'' S - 61º 51' 20'' O), Fuente: Ignacio Ducos. (Criadero El Cencerro) -- Localidad: Anguil, Fuente: Alexandra Dillchneider, Andrea Figueruelo, Donato Fossaceca, Pablo Sphan, Jose Maria Busch, Agustin Fossaceca